2016
DOI: 10.1186/s13018-016-0478-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic results after plaster cast fixation for 10 days versus 1 month in reduced distal radius fractures: a prospective randomised study

Abstract: BackgroundThe aim of this study was to examine whether reduced distal radius fractures can be treated with early mobilisation without affecting the radiographic results.MethodsIn a prospective randomised study, 109 patients (mean age 65.8 (range 50–92)) with moderately displaced distal radius fractures were treated with closed reduction and plaster cast fixation for about 10 days (range 8–13 days) followed by randomisation to one of two groups: early mobilisation (n = 54, active group) or continued plaster cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The radiographic results of this study have already been published (31). Both groups were equally reduced after admission.…”
Section: Discussionsupporting
confidence: 58%
“…The radiographic results of this study have already been published (31). Both groups were equally reduced after admission.…”
Section: Discussionsupporting
confidence: 58%
“…The studies by Davis and Buchanan, 24 Jensen, 25 and Stoffelen and Broos 26 also found no increase in secondary displacement with 1 week of plaster cast immobilization for nondisplaced and minimally displaced fractures. However, the study of Christersson and colleagues 27 shows that moderately displaced DRF, treated with closed reduction and plaster cast immobilization for 10 days, resulted in an increased number of secondary displacements. This is supported by the study of Jung and colleagues who described that greater displacement on the initial radiographs gives a higher possibility of early redisplacement (within 2 weeks after injury).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we believe that the greater the degree of radial displacement of Colles fractures before reduction, the more severe the injury and the easier to ignore the reduction of the radial displacement direction is the basis of its displacement. The contractile activity of soft tissues such as the muscles of the affected limb provides adverse stress for its displacement tendency [19] . The xation mechanism of the splint cannot counteract the pulling force of the muscles on the distal fragment, resulting in displacement of the fracture after xation.…”
Section: Discussionmentioning
confidence: 99%